(untitled) (Research, Society and Development, 2022)
Objective: to map educational technologies for self-care in Diabetes Mellitus in children and adolescents at school. Methodology: The guidelines of the Joana Briggs Institute and the checklist of the Preferred Reporting Items for Systematic and Meta-Analyses - Extension for Scoping Reviews were used. For the search, the MEDLINE databases will be used, via PubMed, and LILACS, SciELO and BDENF, via the Virtual Health Library, in which the studies will be screened and analyzed for inclusion in the review, according to the pertinence and resolution of the guiding question. This protocol will present evidence, strategies and interventions for the development or improvement of educational technologies on diabetes mellitus self-care for children and adolescents, and was registered in the Open Science Framework under No. 10.17605/OSF. IO/UA9J2.